2001
DOI: 10.3354/meps212089
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial dynamics during the transition from spring bloom to oligotrophy in the northwestern Mediterranean Sea: relationships with particulate detritus and dissolved organic matter

Abstract: The variability in microbial communities (abundance and biomass), bacterial production and ectoaminopeptidase activity, particulate and dissolved organic carbon (POC, DOC), and particulate and dissolved lipids was examined in spring 1995 in the northwestern Mediterranean, where a transition from the end of a bloom to pre-oligotrophic conditions was observed. Four time series of 36 h each and 4 h sampling intervals were performed at 5 m and at the chlorophyll maximum (30 m) between 11 and 31 May. Simultaneous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 72 publications
6
35
0
Order By: Relevance
“…Abundance of bacteria was lower than that found in bloom and post-bloom conditions in this area Van Wambeke et al, 2001). Bacterial production, in carbon units averaged about 29 mg C m −2 d −1 over the top 150 m of the water column , equivalent to 0.2 mg C m −3 , suggesting that bacterial production was very low relative to both total bacterial biomass and phytoplankton production.…”
Section: The Microbial Loopmentioning
confidence: 85%
See 1 more Smart Citation
“…Abundance of bacteria was lower than that found in bloom and post-bloom conditions in this area Van Wambeke et al, 2001). Bacterial production, in carbon units averaged about 29 mg C m −2 d −1 over the top 150 m of the water column , equivalent to 0.2 mg C m −3 , suggesting that bacterial production was very low relative to both total bacterial biomass and phytoplankton production.…”
Section: The Microbial Loopmentioning
confidence: 85%
“…This permitted some interesting comparisons to be made between the variability encountered and that recorded during a previous multi-disciplinary study carried out during the spring to summer transition in 1995 detailed in Andersen and Prieur, 2000;Copin-Montégut, 2000;Goutx et al, 2000;Pérez et al, 1997Pérez et al, , 2000Stemmann et al, 2000;Vidussi et al, 2000;Andersen et al, 2001a, b;Van Wambeke et al, 2001. Below we will first very briefly review the cruise plan then highlight some of the findings described in detail in the individual papers of this special section.…”
mentioning
confidence: 99%
“…These results together with hypothesis mentioned above suggest that bacterial abundance and production was not directly linked to the diel changes in dissolved organic matter produced by phytoplankton (bottom-up control), thus reinforcing the role of top-down control by predation or viral lysis in our sampling conditions. At the DYFAMED station, diel changes in bacterial production was also observed during spring phytoplanktonic bloom (Ghiglione et al 2007), but not during spring to summer transition (Van Wambeke et al, 2001). Such discrepancy can result from seasonal factors or meteorological conditions (rain, cloudy days, wind) that could superimpose their effects on diel variability and consequently, probably prevent us from obtaining reproducible diel patterns (Coffin et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal variations of the biogeochemical production regimes have been well studied in this area: deep convection occurs during winter leading to a spring bloom; oligotrophic conditions prevail during summer while perturbations in the meteorological forcing generate a secondary bloom in autumn (Marty, 2002). The vertical and temporal dynamics of heterotrophic bacteria (Van Wambeke et al, 2001;Lemée et al, 2002;Tanaka and Rassoulzadegan, 2004;Misic and Fabiano, 2006) and the contribution of particle-attached bacteria (Turley and Stutt, 2000;Harris et al, 2001) have already been reported in the NW Mediterranean Sea. In a previous study, we have shown that the contribution of attached bacteria to total bacterial activity can reach up to 83% under mesotrophic condition, then reinforcing the biogeochemical role of this fraction in the cycling of particulate organic carbon in the NW Mediterranean Sea (Ghiglione et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Evolution of composition during settling-Although previous studies report on the role of bacterial decomposition of particles by bacteria attached to settling or suspended particles at DYFAMED (Sempéré et al 2000;Van Wambeke et al 2001;Ghiglione et al in press), the MedFlux experiment is the first decomposition study using natural settling marine particles separated by settling velocity. As the particles with different settling velocity decomposed, their compositions changed with time, yet those compositional changes were related to initial com- Table 7.…”
Section: Biodegradability Of the Different Settling Velocity Classes-mentioning
confidence: 99%